DEVELOPMENT OF EVOLUTIONARY ALGORITHM FORMULTICRITERIA OPTIMIZATION IN ASSEMBLY BASEDSHOP - Aravind yuvaraj,K.Ganesan, Balamurugan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Effective inventory management is a crucial aspect of a successful business practice. Theinventorymanagementisneededasbeingaportionofsupplychainnetworktoguardthemanufacturing program towards any type of disturbance. Moreover, it also prevents the system fromworking outofstock,componentsandproducts Inventory mismanagement can be detrimental to a business, especially considering the weight theseitems carry. Inventories that run out of control can lead to significant losses that the company may notbe able to recoup. Considerable investment is required to develop adequate stock. Poorly managedsuppliesleadtoprofitloss. In this paper it is proposed to carry out the development of multi criteria algorithm for a specific casestudy. These heuristicsare testedandinferenceswillbe made